Virtual training, real effects: a narrative review on sports performance enhancement through interventions in virtual reality - Richlan, Fabio; Weiß, Moritz; Kastner, Patrick; Braid, Jeremias (Frontiers in Psychology, 2023)
The present article reports a narrative review of intervention (i.e., training) studies using Virtual Reality (VR) in sports contexts. It provides a qualitative overview and narrative summary of such studies to clarify the potential benefits of VR technology for sports performance enhancement, to extract the main characteristics of the existing studies, and to inform and guide future research. Our literature search and review eventually resulted in 12 intervention studies with a pre vs. post design focused on different sports, including target and precision sports (archery, bowling, curling, darts, golf), bat/racquet and ball sports (baseball, table tennis), goal sports (football/soccer, basketball), martial arts (karate), and sport-unspecific processes such as bodily sensations and balancing. The samples investigated in the primary studies included novice, amateur, and expert athletes (total aggregated sample size N = 493). Many studies found statistically significant effects in relevant target skills following interventions in VR, often outperforming training effects in passive or active control conditions (e.g., using conventional training protocols). Therefore, interventions in VR (or extended reality) have the potential to elicit real effects in sports performance enhancement through training of motor and psychological skills and capabilities in athletes, including perception-action skills, strategic, tactical and decision-making, responding to unexpected events, and enhancing psychological resilience and mental performance under pressure. The neurocognitive mechanisms (e.g., visual search behavior, imagery), methodological aspects (e.g., adaptive training difficulty), and the issues of real-world transfer and generalizability via which these potential sports-performance-related improvements may occur are discussed. Finally, limitations of the present review, the included studies, the current state of the field in general as well as an outlook and future perspectives for research designs and directions are taken into consideration.